An introduction to cryptography - Mollin, Richard A. 1947- (CRC Press series on discrete mathematics and its applications, 2000)
"An Introduction to Cryptography is intended for the person wanting an introduction to the subject of cryptography, however, it contains enough advanced, optional material to challenge even the informed reader." "Beginning with an overview of the history of cryptography, the author then covers the basics of computer arithmetic and explores complexity. The author then presents comprehensive information on symmetric-key cryptosystems, public-key cryptosystems, and primality testing. He illustrates all methods with worked examples and includes a full description of the numerous cryptographic applications."--Jacket.